COVID-19, networks and sport. Issue 1 (4th March 2022) - Parnell, Daniel; Widdop, Paul; Bond, Alex; Wilson, Rob
ABSTRACT: This commentary serves to provide a rapid analysis of the impact of coronavirus disease 2019 (COVID-19) on sporting mass gatherings. The focus of this commentary surrounds sporting mass gatherings and strategies to mitigate the spread of COVID-19, with a particular focus on the UEFA EURO 2020 competition. Further references to the 2020 Olympic Games, and community recreational football are made. The intention is to stimulate discussion, analysis, interest and research on what the initial impact of COVID-19 has on sport. COVID-19 could fundamentally change the way sport operates in the future and requires further analysis. We hope this commentary provides an interesting record and reference point for future research and practice of those operating in sporting organisations. Learning lesson from this crisis, must ensure sport managers and practitioners are better prepared in sport and society for similar events in the future.